PROFESSIONAL TRAINING IN PHYSICAL EDUCATION: AN INNOVATIVE EXPERIENCE (Fiep Bulletin - online, 2017)
This article presents the Professional Training Project course Bachelor / Degree in Physical Education from theUniversity Vila Velha the academic community as a contribution to the stage specificity of discussion in the bachelor's degree.Therefore, it was considered the guidelines established by the Ministry of Education and also by the higher education institution inquestion. Other references used reveal the specifics of the stage and its innovative character. Qualitative research ofdocumentary character used portfolios as corroborative sources of innovative stage action. The stage model presented orientsacademic for professionalism and allows entering the labor market glimpsing a future project or job in the areas of leisure, sport orfitness and physical training.